Transfer Of Power: Mitch Rapp # 3 - Flynn, Vince, 1966-2013 (New York : Emily Bestler Books, Atria, 2020)
When a gang of terrorists seizes control of the White House, taking hostages, leaving many dead, and driving the president to a secret bunker, it is up to the CIA's top counterterrorism specialist, Mitch Rapp, to stop the insurrection.
new book 2023 winter.
Keywords: Rapp, Mitch -- (Fictitious character) -- Fiction; Attempted assassination -- Fiction; Presidents -- Fiction; Terrorism -- Fiction; Washington (D.C.) -- Fiction; Thriller fiction; Political fiction